2016
DOI: 10.21699/jns.v5i4.461
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Duodenal Obstruction in Neonates: Over 13 Years’ Experience from a Single Centre

Abstract: Aim: To study the prevalence of associated anomalies with neonatal duodenal obstruction and factors impacting short-term survival. Material and methods: Records of 31 neonates with neonatal duodenal obstruction could be retrieved and analyzed for a 13.5-year-period (October 2003-May 2016). M:F ratio was 1.58:1. The mean birth weight was 2.15 kg; 12 patients were preterm. Etiologies included duodenal atresia (n=23), duodenal web (n=8) and malrotation of gut (n= 6). Results: Associated anomalies were seen in 19/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
22
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 10 publications
7
22
2
6
Order By: Relevance
“…In this study, 14 patients (23.3%) were aged between 30 days and 12 months, and 2 patients (3.3%) were diagnosed after the age of one year. This study reported a male gender predilection (M:F=1.14:1), same finding was seen in Parveen Kumar et al 9 and Kamal et al studies 11 .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In this study, 14 patients (23.3%) were aged between 30 days and 12 months, and 2 patients (3.3%) were diagnosed after the age of one year. This study reported a male gender predilection (M:F=1.14:1), same finding was seen in Parveen Kumar et al 9 and Kamal et al studies 11 .…”
Section: Discussionsupporting
confidence: 87%
“…This study reported a mortality rate of CDO to be 11.7%, which is comparable to many studies from the developing countries, Rattan et al 20 had reported mortality of 11 (13.5%) out of 81 neonates, Parveen Kumar et al study 9 reported 22.5% mortality and Zamir et al 21 had reported mortality of 58% in a study from Pakistan. In the developed countries, antenatal diagnosis and timely intervention to correct CDO, postoperative outcome is much better than developing countries 22,23 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Синдром Дауна -это распространенная генная патология (1:650-1000), обусловливающая наличие врожденных пороков развития различных органов и систем, в том числе желудочно-кишечного тракта [1][2][3][4]. Среди пороков пищеварительной системы у больных синдромом Дауна чаще, чем в общей популяции, выявляют атрезию пищевода, стеноз и атрезию двенадцатиперстной кишки, незавершенный поворот кишечника, кольцевидную поджелудочную железу, болезнь Гиршпрунга, атрезию ануса [2][3][4][5][6].…”
unclassified